Pengaruh Budaya Organisasi Dan Kepemimpinan Kepala Sekolah Terhadap Kinerja Guru di SMA Negeri 9 Kota Jambi - Benar Sembiring; Redi Indra Yudha; Krisdayani Krisdayani (Jurnal Ilmiah Dikdaya, 2020)
In general, the application of the concept of organizational culture in schools is actually not much different from the application of other organizational culture concepts. Even if there are differences, it may only lie in the type of dominant value it develops and the characteristics of its supporters. This is because the values developed in schools, of course, cannot be separated from the existence of the school itself as an educational organization, which has a role and function to try to develop, preserve and pass on cultural values to students in the school environment.Based on the results of research that has been carried out with data collected both through questionnaires and separate data collection processes (interviews, observation, and documentation), a conclusion is obtained which states that organizational culture and principal leadership together have positive values and affect teacher performance in SMA Negeri 9 Jambi City. This means that teacher performance does not only come from how a teacher is able to carry out the tasks assigned to him, but how the conditions and work environment are so that they are able to give their best.Thus, overall teachers can work well not only supported by the existence of complete learning facilities and facilities, but also several other factors. This is because the high or low performance of a teacher is none other than due to an underlying drive or need to be able to carry out their work load and responsibilities properly.